Capacidade dos índices antropométricos e de obesidade central para identificação de participantes com alto risco cardiovascular em longo prazo na coorte de Universidades Mineiras (CUME) - Thais Moreira Nascimento Lima (2019)
Cardiovascular Diseases (CVD) stand out as the leading causes of death by Non-Communicable Diseases (NCD) worldwide, representing a relevant public health problem. To estimate the risk of developing CVD, were created the so-called risk algorithms based on regression analyzes of population studies, of which the most commonly used is the 10-year Framingham Risk Score. However, the applicability of such scores to clinical practice has been limited, as the measurements of several components are required for their calculations. Thus, simpler anthropometric and central obesity indexes have been proposed for the identification of participants with high cardiovascular risk. This is an epidemiological, cross-sectional and analytical study conducted with the objective of analyzing the ability of anthropometric and central obesity indexes to identify participants with high cardiovascular risk in a long-term perspective at the Cohort of Universities of Minas Gerais (CUME). The sample consisted of 144 participants from the validation study of metabolic syndrome and its components in the CUME study, male and female applicants aged between 30 and 59, from which were collected demographic, socioeconomic, anthropometric, and lifestyle data and performed biochemical analyzes. Cardiovascular risk was calculated using the four versions of the 30-year Framingham Score (two for general CVD and two for severe CVD). Afterwards, were evaluated the ability of Body Mass Index (BMI), Waist Circumference (WC), Conicity Index (CI), Visceral Adiposity Index (VAI) and Lipid Accumulation Product (LAP) to identify high cardiovascular risk. Statistical analysis was performed using correlation tests, such as the Pearson, Spearman and ROC curve , with a level of statistical significance of 5%. Most participants were classified with low cardiovascular risk. All anthropometric and central obesity indexes presented positive, moderate (except for VAI) and significant correlations with the Framingham Risk Score when considering the total population. WC was the best predictor for all outcomes, except for the cardiovascular risk for severe CVD calculated with the BMI, in which the CI was highlighted. It is important that these findings are considered in order to simplify the detection of cardiovascular risk, allowing early knowledge of the situation of high-risk population groups and establishing measures of prevention, control and treatment of CVD and, consequently, the reduction of NCD.